The use of collocations by advanced learners of English and some implications for teaching - Nesselhauf, Nadja (Applied linguistics, 2003)
Although it is widely acknowledged that collocations are both indispensable and problematic for language learners and that they therefore should play an important part in second language teaching, especially at an advanced level, learners' difficulties with collocations have not been investigated in much detail so far. This paper reports on an exploratory study that analyses the use of verb-noun collocations such as take a break or shake one's head by advanced German‐speaking learners of English in free written production. First, an attempt is made to define ‘collocations’ as precisely as possible, and the methodology that has been developed for analysing learner collocations in free production is described. Then, the types of mistakes that the learners make when producing collocations are identified and the influence of the degree of restriction of a combination and of the learners' L1 on the production of collocations is investigated. While the degree of restriction emerges to have some, but comparatively little, impact on the difficulty of combinations for the learners, the learners' L1 turns out to have a degree of influence that goes far beyond what earlier (small‐scale) studies have predicted. Finally, the implications of these results for teaching are discussed, most importantly the role of L1‐L2 differences.